Analisis Pengaruh Performa PageSpeed terhadap Optimasi SEO Website PT. Bmar$ - Qurrotu A’yun; Paula Dewanti (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
The Fourth Industrial Revolution has reshaped the way industries operate by integrating advancedinformation technologies into nearly every aspect of business. The convergence of physical, digital,and biological systems has created a new landscape where websites serve as a central platformfor marketing and promotion. Their ability to reach wide audiences, provide instant access toinformation, and reduce operational costs makes them highly effective tools for business growth.At the same time, the crowded digital marketplace poses new challenges, particularly in ensuringthat Websites remain visible in search engine results. Search Engine Optimization (SEO) hastherefore become an essential strategy to secure stronger rankings and sustain audienceengagement. Without effective SEO, Websites risk lower visibility, reduced traffic, and limitedpromotional impact. This study explores the analysis and optimization of SEO practices to improvewebsite performance and enhance competitiveness in today’s fast-evolving digital industry.